Perlindungan Konsumen PT. Indonesia Air Asia Terkait Pembatalan Tiket Penerbangan Ditinjau Berdasarkan Undang-Undang Perlindungan Konsumen - Gurnita, Shafira Tri (Acta Comitas : Jurnal Hukum Kenotariatan; Vol 7 No 03 (2022), 2022)
This study aims to determine the form of protection for PT Indonesia Air Asia passengers who are victims of flight ticket cancellations and legal remedies that can be taken by passengers based on the perspective of consumer protection law. This study uses a normative research method with a statutory approach through access to data that is not limited to books, but also articles and journals, as well as other literature related to the problem under study. The results of the study and the conclusions obtained from this study are that legal protection for consumers of PT Indonesia Air Asia is guaranteed in Article 7 of Law Number 8 Year 1999 concerning Consumer Protection that consumers are entitled to compensation due to flight ticket cancellations. If this compensation is not carried out, PT Indonesia Air Asia may be subject to administrative sanctions. The settlement efforts that can be done by consumers can be in the form of non-litigation and litigation .